Pendapatan, Beban Usaha, Tingkat DETERMINANTS ANALYSIS OF PROFITABILITY MANUFACTURING COMPANIES IN GARMENT AND TEXTILE SUB SECTOR PERIOD 2018 - 2020 - Mohammad Taufiq; Han Tantri Hardini; Macfudzil Asror (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
This study aims to determine the effect of income and operating expenses on the level of profit in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the Garment and Textile Sub-Sector in the 2018-2022 period, both partially and simultaneously analyzed. The population of this study is the financial statements of manufacturing companies in the garment and textile sector for the period 2018-2022 through the official website of the Indonesia Stock Exchange on the page www.idx.co.id. Meanwhile, the research sample was taken using the non-probability sampling method. The technique taken from non-probability sampling is purposive sampling. Then there were 13 garment and textile manufacturing companies listed on the IDX in 2018-2020 that matched the sample selection criteria, then multiplied by 3 years of reporting period so that the sample used was 39 samples. The data analysis in this research uses multiple linear regression analysis with the help of SPSS version 25 program (Statistical Package for Social Science). Several requirements that must be met before carrying out multiple regression analysis are the classical assumption test composed of autocorrelation test, normality test, and multicolonier test. The hypothesis test is a joint hypothesis test and a partial hypothesis test. Together, the hypothesis testing was carried out with the F-test. while partially, hypothesis testing is done by T-test. The results of statistical analysis show that the Income variable (X1) has no effect on the Net Profit variable (Y). So it can be interpreted if if income increases by 1% then net profit will decrease. In addition, this study also shows that the operating expense variable (X2) has no effect on net income. So it can be interpreted if if income increases by 1% then net profit will decrease. The results of simultaneous research between variables, show that the income (X1) and operating expenses (X2) variables together have no effect on net income.